A CAD tool to support idea generation in the product planning phase. Issue 4 (3rd July 2016) - Bacciotti, Daniele; Borgianni, Yuri; Rotini, Federico
ABSTRACT: The work described in the paper is motivated by the lack of computer-aided tools to support Product Planning and, more specifically ideation processes of New Product Development (NPD) initiatives. The domain is populated by software applications aimed at managing and organizing Product Planning activities, which thus poorly contribute to the definition of new product characteristics, and models to stimulate novel ideas. The latter face limitations in terms of overlooked implementation with CAD tools supporting the following NPD phases and poor exploration of the design space. The authors propose an original method and software prototype capable to provide a wide range of stimuli, whose testing demonstrated much better results than traditional approaches in terms of quantity and variety of generated ideas. GRAPHICAL ABSTRACT: